Building an ethical learning community in schools - Bergmark, Ulrika (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2009)
The overall aim of this thesis was to explore the school as a site for ethical practice. Specific objectives were to elucidate, encourage understanding for, and discuss: (i) teachers' and students' lived experience of ethical situations in school, (ii) teachers' and students' working together to promote learning in subjects and also to develop an ethical attitude towards society and the way people interact, and (iii) teachers' and students' working together to create an appreciative and positive climate in school. The research was conducted in a secondary school in Northern Sweden, which participated in a school improvement process, entitled Full of Value. The process has aimed at promoting learning through the development of an ethical attitude. This involves both the psycho-social and the physical community of the school.The research was inspired by life-world phenomenology. A total of 45 teachers and 45 students participated in the study. To create empirical data, the following methods have been used: written reflection, interview, close observation, and photo documentation. Through empirical findings during the research process, some parts of the research were inspired by participatory and appreciative action research (PAAR).The thesis consists of five part studies, published in international pedagogical journals. The findings show essential values for teachers and students in school, such as: openness, communication, trust, respect, care, empathy, truth, justice, appreciation, participation, and mutual learning.Teachers' and students' experiences of school as a site for ethical practice imply the value of: striving for ethical awareness, building ethical relationships, and encouraging ethical actions. The findings in this thesis suggest that the schools' mission to integrate ethics into the curriculum can be viewed as a process whereby, together with students in different educational settings, an ethical learning community can be created and sustained.